Properties and Bioactivity of Carrageenan, Myofibril, and Collagen-Based Smoked Edible Films - MONTOLALU, Roike Iwan; DIEN, Henny Adeleida; MENTANG, Feny; TAHER, Nurmeilita; BERHIMPON, Siegfried (Nutrición Clínica y Dietética Hospitalaria, 2024)
The objective of this study is to develop and evaluate the properties of smoked edible film (EF) composed of carrageenan, myofibril, and collagen. The smoked EF was prepared by incorporating 0.8% liquid smoke. The analysis focused on various parameters including pH, physical properties such as thickness, solubility, tensile strength, elongation percentage, and water vapor transmission rate (WVTR). Sensory evaluation was also conducted to assess the texture attributes of the coated product, including wateriness, firmness, elasticity, hardness, and juiciness. The findings revealed that the concentration of the ingredients influenced the thickness of the EF, with myofibril proteins exhibiting higher concentrations compared to carrageenan and collagen. Both collagen and myofibril demonstrated maximum solubility at a concentration of 6%, while carrageenan achieved optimal solubility at concentrations ranging from 2 to 2.5%. Carrageenan exhibited significantly higher tensile strength compared to myofibril and collagen, whereas collagen demonstrated greater elasticity than carrageenan and myofibril protein. Moreover, myofibril protein film exhibited a lower water vapor transmission rate compared to carrageenan and collagen films. In terms of sensory assessment, carrageenan displayed high elasticity and juiciness, while collagen and myofibril showed high firmness and hardness. All EFs showed better antioxidant activity compared to Trolox (EC50 < 95.57 µg/mL).